Enhancing EFL Students’ Reading Comprehension Through Directed Reading Thinking Activity (DRTA) - Muhammad Amin; Dhian Puspita Ayu; Yudi Mahbub (Explorations in English Learning, 2025)
This study explored the effectiveness of the Mediated Instruction of Text (MIT) strategy in improving reading comprehension among tenth-grade EFL students through a one-group pre-test–post-test pre-experimental design with 36 participants. The MIT approach focused on teacher-guided meaning-making, strategic reading, and contextual understanding to help students engage more deeply with texts. A multiple-choice reading comprehension test was given before and after the instruction to measure student progress. Data analysis using a paired samples t-test in SPSS 17 showed a statistically significant improvement in reading scores, with the mean rising from 10.08 (pre-test) to 14.94 (post-test), t(35) = 8.63, p < 0.05. These findings suggest that the MIT strategy had a strong positive effect on students’ reading performance. The results support incorporating mediated instructional techniques into EFL reading classes, as such approaches enhance comprehension and promote active learner participation and greater cognitive engagement with texts. MIT shows its potential as a practical and effective teaching model for developing reading skills in EFL settings by fostering deeper understanding and encouraging reflective reading habits.